Study of Aedes aegypti population with emphasis on the gonotrophic cycle length and identification of arboviruses: implications for vector management in cemeteries - Garcia-Rejon, Julian E.; Ulloa-Garcia, Armando; Cigarroa-Toledo, Nohemi; Pech-May, Angelica; Machain-Williams, Carlos; Cetina-Trejo, Rosa Carmina; Talavera-Aguilar, Lourdes Gabriela; Torres-Chable, Oswaldo Margarito; Navarro, Juan Carlos; Baak-Baak, Carlos Marcial (Revista do Instituto de Medicina Tropical de São Paulo, 2018)
Aedes aegypti is the vector of the arboviruses causing dengue, chikungunya and zika infections in Mexico. However, its presence in public places has not been fully evaluated. In a cemetery from Merida, Yucatan, Mexico, the productivity of Ae. aegypti, the gonotrophic cycle, and the presence of Ae. aegypti females infected with arboviruses were evaluated. Immature and adult mosquitoes were inspected every two months between April 2016 to June 2017. For the gonotrophic cycle length, the daily pattern of total and parous female ratio was registered and was analyzed using time series analysis. Ae. aegypti females were sorted into pools and assayed for flavivirus RNA by RT-PCR and Sanger sequencing. Aedes aegypti immatures represented 82.86% (8,627/10,411) of the collection. In total, 1,648 Ae. aegypti females were sorted into 166 pools. Two pools were positive; one for dengue virus (DENV-1) and the other for zika virus (ZIKV). The phylogenetic analysis revealed that the DENV-1 is more closely related to isolates from Brazil. While ZIKV is more closely related to the Asian lineage, which were isolates from Guatemala and Mexico. We report some evidence of vertical transmission of DENV-1 in nulliparous females of Ae. aegypti. The gonotrophic cycle was four and three days in the rainy and dry season, respectively. The cemetery of Merida is an important focus of Ae. aegypti proliferation, and these environments may play a role in arboviruses transmission; probably limiting the efficacy of attempts to suppress the presence of mosquitoes in domestic environments.